Sunflower (Helianthus annuus L.) Seed Hull Waste: Composition, Antioxidant Activity, and Filler Performance in Pectin-Based Film Composites - De'Nobili, Maria D.; Bernhardt, Dana C.; Basanta, Maria F.; Rojas, Ana M. (Frontiers in Nutrition, 2021)
Helianthus annuus L. seed hull is an abundant waste of the edible oil industry. To envisage potential applications of this waste, here, we aimed to analyze the chemical composition of milled sunflower hulls (SP), constituted mainly by 210 m (51.4%) and 420 m (27.6%) average mesh particle sizes. SP contained almost 30% of cellulose, 26.4% of lignin, 38.5% of neutral sugars, mainly hemicelluloses, and only 1.3% of proteins. The important lignin content and low pectin content (4.0% of uronic acids) present in SP were both ascribed to its low hydrophilic behavior and hydration capacity. Phenolic compounds were mostly proanthocyanidins (168 mg/100 g SP), with lower amounts of extractable (31.4 mg/100 g SP) phenolics (O-caffeoylquinic acid), all of them associated with the DPPH radical scavenging capacity (95 mg ascorbic acid equiv./100 g) and ferric reducing power (FRAP: 152 mg ascorbic acid equiv./100 g) shown by SP. Esterified ferulic acid (52.9 mg/100 g SP) was also found, mostly as monomers and trimers. SP of 53 m particle size was then assayed as filler (0, 5, 8, and 12% concentrations) in calcium low methoxyl pectin-based films, which showed antioxidant capacity (DPPH and FRAP assays) in an SP-concentration-dependent manner. SP showed homogeneous dispersion in composite films equilibrated at 57.7% relative humidity. Water content decreased while film thickness increased with SP-concentration. When loaded at a 12% level, the presence of 53-m SP decreased the water vapor permeability and increased the normal stress at film fracture. Sunflower hulls can then be applied to the development of active materials like 12 % SP film, which can be proposed as a food slice antioxidant separator to be investigated in a future work.